HiLesMaker: Diseño de Especificaciones de Alto Nivel Asistida por Computador - Muñoz, Gerardo; Rojas Galeano, Sergio Andrés; Rodríguez Paez, Juan Carlos (Ingeniería, 2000)
The HiLes (High Level Specification) [1] is a tool for algorithmic process design to be running in hardware and software. Since it is a visual language, it must be converted to a executable code for a computing device like a programmable cell, a microprocessor or a micro controller. In this paper we present HiLesMaker, a first prototype of a computational tool that allows for the edition of HiLes diagrams, and generation of symbolic representation of programs that had been designed on it.